Development of insulated cu wire stitch bonding - Leong, H.Y.; Yap, B.K.; Navas, K.; Mohd Rusli, I.; Tan, L.C.; Faiz, M. (2013)
The market demands for higher pin counts and more chips functionality poses challenges in conventional wire bonding. However, the novel insulated Cu wire technology enables fine and ultra fine pitch wire bonding as the insulator coating on the bare wire prevents wires shorting problem. This paper present study on the stitch bonding process optimization and its challenges for the insulated Cu wire with the diameter of 20 urn. Insulated Cu stitch bond samples showed 37 % lowe: stitc~ pull s~rength than that of bare Cu. The crosssectioned insulated Cu stitch bond shows that there are insulation residue between the Cu stitch and the Au plated substrate, potentially resulting low.er stitch pull p~rformance. H~wever, after isothermal aging at 225 DC up to 78 hours, the stitch pull results for Insulated Cu WIfe passed the Industry reliability standard, without any lifted bond. A detailed comparison study was performed for the Insulated Cu and the bare Cu stitch bonding.